Les modèles de répartition des revenus de type intégré : quelques éléments de comparaison - Mayer, Francine (L'Actualité économique)

(untitled) (HEC Montréal, 1983)
AbstractThe purpose of this paper is to examine different types of models dealingwith the question of income distribution. These models can be classified into threecategories: microsimulation models, computable general equilibrium models andintegrated macro-distribution models. In this study, we are concerned with theinvestigation of a few models of each type, the analysis of their essential characteristics and the description of their comparative advantages and disadvantages.